Versatile electrochemical cell for Li/Na-ion batteries and high-throughput setup for combined operando X-ray diffraction and absorption spectroscopy - Serena Margadonna (Journal of Applied Crystallography, 2016)
A fully operational setup (electrochemical cells, sample changer and interfacing software) that enables combined quasi-simultaneous operando X-ray diffraction (XRD) and absorption (XANES and EXAFS) measurements coupled with electrochemical characterization has been realized for synchrotron based studies. Combined XRD, XANES and EXAFS analysis provides a deep insight into the working mechanisms of electrode materials.